Knowledge, Attitude, and Practices towards Covid-19 in the Midst of Pandemics among Jakarta Residents - Christine Tan; Andree Kurniawan; Devina Adella Halim; Felix Wijovi; Jovita Jovita; Cindy Monika Agatha; Christin Soputri; Eva Maria; Sharleen Winata (Journal of Epidemiology and Public Health, 2020)
Background: Jakarta, capital city of Indonesia, had been extremely hit by the COVID-19 pandemic. Public consistence with control measures was important, which was greatly affected by knowledge, attitudes and practices towards COVID-19. This study aimed to investtigate knowledge, attitudes and practices of Jakarta residents for COVID-19.Subjects and Method: This was an analytic observational study with a cross-sectional design. Sample was gathered online from 221 Jakarta residents, range in age 10 to 60 years, which use self-reported questionnaires consisting of consent, questions about sociodemographics, knowledge, attitudes and practices relevant to COVID-19 and analyzed using t-test and ANOVA. A linear regression analysis was conducted to identify factors associated with knowledge, attitude and practice. Results: Participants showed moderate level of knowledge (mean= 71.20; SD= 8.37), positive attitudes (mean= 53.47; SD= 5.10) and moderate practice (mean= 78.63; SD= 12.73). Results demonstrated that women have better knowledge (mean= 72.1; SD= 9.0; p= 0.360), optimistic attitudes (mean= 55.1; SD = 6.2; p= 0.005) and great practices (mean= 80.1; SD= 11.6; p= 0.316) towards COVID-19 than men. Elderly have better knowledge (mean= 75.6; SD= 5.0; p= 0.001), optimistic attitude (mean= 56.3; SD= 3.8; p= 0.033) and good practices (mean= 82.4; SD= 14.3; p= 0.301) than younger individuals.Conclusion: Directed approaches in health promotion should be integrated for vulnerable populations, such as men, younger people, and low-income earners who would be at greater risk of COVID-19.Keywords: COVID-19, knowledge, attitude, practiceCorrespondence: Andree Kurniawan. Department of Internal Medicine, Faculty of Medicine Pelita Harapan University. Boulevard Jenderal Sudirman, Karawaci, Tangerang, Banten, Indonesia 15811. Email: andree.kurniawan@uph.edu. Mobile: +62-815-8891-655.Journal of Epidemiology and Public Health (2020), 05(04): 477-488https://doi.org/10.26911/jepublichealth.2020.05.04.10